Penerapan Relaksasi Benson Kombinasi Unsur Keyakinan untuk Menurunkan Kecemasan pada Pasien CKD yang Menjalani Hemodialisa: Studi Kasus - Rovi Apriani Eka Suci; Laili Nur Hidayati (PSIK FKKMK UGM, 2023)
Background: Benson relaxation is one of non-pharmacological therapies that helps patients deal with their anxiety, thus becomes a viable option. By reducing the body’s need for oxygen and allowing the muscles to relax, the Benson Relaxation Technique which is combined with belief elements, may induce comfort and peace feelings.Objective: To evaluate the effectiveness of the Benson relaxation therapy intervention with the combination of belief elements to reduce anxiety in a CKD patient who was receiving hemodialysis. Case report: A 70-year-old man was diagnosed with chronic kidney disease (CKD) stage V. After the first hemodialysis, this patient had complained about his feeling of limp, nausea, and queasy body, fear and anxiety about his condition, and restless sleeping. Patient was given Benson relaxation technique with the combination of elements of belief for 3 days as his main intervention.Outcome: Following the use of the Benson relaxation treatment and a combination of belief elements in the form of zikir (praising to God) and istigfar (apologizing toward God) for twice a day for three days, the result had shown a decrease in HARS score from 23 (moderate anxiety) to 15 (mild anxiety).Conclusion: Patients with CKD can effectively reduce anxiety with non-pharmacological Benson relaxation therapy using a combination of beliefs elements.ABSTRAKLatar belakang: Penanganan kecemasan dapat menggunakan terapi non-farmakologi, salah satunya dengan relaksasi Benson. Teknik Relaksasi Benson dapat menghambat aktivitas saraf simpatis sehingga mengurangi penggunaan oksigen oleh tubuh dan menyebabkan otot-otot menjadi rileks serta menimbulkan perasaan tenang dan kenyamanan.Tujuan: Mengetahui efektivitas intervensi terapi relaksasi Benson dengan penambahan unsur keyakinan untuk menurunkan kecemasan pada pasien CKD yang sedang menjalani hemodialisis.Laporan kasus: Seorang laki-laki berusia 70 tahun dengan diagnosa chronic kidney disease (CKD) stadium V. Kondisi pasien setelah melakukan hemodialisis pertama mengeluhkan lemas, mual, muntah, takut dan cemas dengan kondisinya, serta mengeluh tidak bisa beristirahat dengan tenang. Pasien diberikan intervensi utama relaksasi Benson dengan penambahan unsur keyakinan selama 3 hari.Hasil: Setelah dilakukan pemberian intervensi terapi relaksasi Benson dengan penambahan unsur keyakinan seperti berzikir dan beristigfar selama 3 hari dengan frekuensi 2 kali sehari, didapatkan hasil penurunan skor HARS dari 23 (kecemasan sedang) menjadi 15 (kecemasan ringan).Simpulan: Terapi relaksasi Benson dengan penambahan unsur keyakinan efektif untuk menurunkan kecemasan pasien CKD.